Determination of nitrofurans metabolites residues in aquatic products by ultra-performance liquid chromatography–tandem mass spectrometry. (1st February 2016) - Zhang, Yibei; Qiao, Haiou; Chen, Chen; Wang, Zhilun; Xia, Xiaodong
Highlights: A method is proposed for simultaneous detection of four NFs metabolites in aquatic products. The correlation coefficient ( R 2 ) for matrix calibration curve, in the range of 1–100 ng ml −1, was above 0.99. Recovery rates and RSD ranged from 88% to 112% and from 2% to 4%, respectively. LOD and LOQ for all four metabolites were 0.5 μg kg −1 and 1.5 μg kg −1, respectively. Abstract: A method was described for monitoring four nitrofuran metabolites including 5-methylmorpholino-3-amino-2-oxazolidinone (AMOZ), 3-amino-2-oxazolidone (AOZ), 1-amino-hydantoin (AHD) and semicarbazide (SEM) in aquatic products. The analytes were quantified by ultra-performance liquid chromatography–tandem mass spectrometry operating in positive ion multiple monitoring mode (MRM) after 2-nitrobenzaldehyde derivatization. The matrix calibration curve was established with correlation coefficient ( R 2  > 0.99) in the range of 1–100 ng ml −1 . Limit of detection and limit of quantification for all analytes were 0.5 and 1.5 μg kg −1, respectively. Recovery rates and relative standard deviations ranged from 88% to 112% and 2% to 4%, respectively. The validated method was successfully applied to detect nitrofuran metabolites in 120 fish samples. The analytes were detected in 6/16 species of fish samples, with a total detection rate of 6.5%. AOZ was most frequently detected (8.3%), followed by AMOZ (7.5%), AHD (5.0%) and SEM (5.0%). The method is proposed for monitoring nitrofuran metabolites in aquatic products.